Managing Elevated Intracranial Pressure as the Complication of Angiomatous Meningioma - Adriana Damayanti; Tiara Aninditha; Henry Riyanto Sofyan; Irma Savitri; Rahmad Mulyadi; Mohamad Saekhu (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Introduction: Meningioma is the most common central nervous system primary tumor, which can grow at the cranial base. Angiomatous meningioma, with a prevalence of 2.1%, is classified as the World Health Organization (WHO) grade I meningioma. Although considered benign, it has high Vascular Endothelial Growth Factor (VEGF) activity. Case Report: A 41-year-old woman presented with clear nasal discharge upon sitting, progressive headaches, blurred vision, and right-sided hemiparesis following prior surgeries for angiomatous meningioma. Initial symptoms included episodic headaches, later worsening with visual impairment and motor deficits. She underwent decompressive craniectomy, VP shunt placement for hydrocephalus, and cranioplasty but had a functional decline. Examination revealed decreased consciousness, anisocoria, right facial nerve palsy, spastic hemiparesis, and pressure ulcers. Imaging confirmed tumor progression with uncal herniation and hydrocephalus. After infection management, VP shunt revision improved her condition, and tumor resection was planned. The prognosis remained poor regarding survival, function, and recovery. Discussion: Although considered benign, it has high activity of Vascular Endothelial Growth Factor (VEGF). Massive peritumoral edema may lead to complications by increasing intracranial pressure (ICP). The management of elevated ICP includes tumor resection, cerebrospinal fluid (CSF) diversion, and administration of anti-edema agents. Due to its challenging access and proximity to vital structures such as cranial nerves and blood vessels, determining an appropriate management strategy poses a significant challenge to avoid disability. Conclusion: Skull base meningioma in women aged 40–70 poses a high risk of complications and disability if mismanaged, especially angiomatous meningioma with high vascularity despite being WHO Grade I.